‘E sí la hoïren tots’: sí and emphatic positive polarity in Old Catalan - Afra Pujol Campeny (Universitat Autònoma de Barcelona, 2020)
This paper explores the semantic value and syntactic distribution of the lexical item sí in Old Catalan. After examining data extracted from El Llibre dels Fets, a 13th century chronicle, it is concluded that sí was an Emphatic Positive Polarity Particle (EPPA) whose appearance was restricted to non-veridical contexts already in this period. This finding strongly contrasts with analyses put forward for sí in Old Catalan and Old Spanish, that date its grammaticalization as an (EPPA) two centuries later, and with analyses of sí in other Old Romance languages, where it has been linked to the satisfaction of the V2 parameter.